MENINGKATKAN EFISIENSI DALAM REKONSILIASI KAS ATM: IMPLEMENTASI SISTEM INFORMASI BERBASIS WEBSITE - Hesananda, Rizki; Mulyawan, Yudhi (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2024)
This research aims to develop a web-based ATM cash reconciliation information system at PT. Bank Rakyat Indonesia, Tbk. Currently, the ATM cash reconciliation process is manually performed using Excel files, which are prone to errors and time-consuming. In this context, the development of an information system is crucial to enhance the efficiency and accuracy of the reconciliation process. The research methodology employed the Waterfall software development model. The stages of the research included requirements analysis, system design, implementation, and testing. Data were collected through interviews, observations, and document analysis from the ATM Cash Reconciliation Division. The system implementation utilized PHP for web development and MySQL as the database. The results of the study indicate that the implementation of the system successfully reduced the reconciliation process time from an average of 35 minutes to just 8 minutes per case. The system also improved data accuracy and enhanced information accessibility for involved staff. Another advantage is the reduction in potential human errors that frequently occurred in the previous manual process. Despite achieving significant advantages, the implementation of this system also faced challenges in adopting new technology and existing technological limitations. These challenges require change management strategies and continuous improvement to support optimal system use in the future. In conclusion, the implementation of the web-based ATM cash reconciliation information system at PT. Bank Rakyat Indonesia, Tbk. provides a significant contribution to improving efficiency, accuracy, and data accessibility. This system has the potential to serve as a strong foundation in supporting the operations of the ATM Cash Reconciliation Division in the company.